2014
DOI: 10.1016/j.jnim.2014.10.077
|View full text |Cite
|
Sign up to set email alerts
|

Salt and hypertension in rural and urban populations of low to middle income countries: A systematic review and meta-analysis

Abstract: Results:We found no evidence of reduced depression (p ¼ 0.339), reduced anxiety (p ¼ 0.862), higher flourishing (p ¼ 0.453), higher positive moods (p ¼ 0.518) or lower negative moods (p ¼ 0.538) in the treatment group compared to the control group. Wellbeing trajectories over the study period were similar for the two groups. Sensitivity analyses did not show an effect for those with low starting vitamin D or wellbeing either. Conclusions: Supplemental vitamin D may not be suitable and needed for improving psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
5
15
0
3
Order By: Relevance
“…These studies are summarized in Table . The outcomes examined were diverse: one study assessed mortality outcomes (category I), two studies assessed morbidity outcomes (category II), two studies assessed outcomes related to symptoms/quality of life/functional status (category III), six studies assessed BP outcomes (category IV), seven studies assessed other clinically relevant surrogate outcomes (category V), and 10 studies assessed physiologic outcomes (category VI) …”
Section: Resultsmentioning
confidence: 99%
“…These studies are summarized in Table . The outcomes examined were diverse: one study assessed mortality outcomes (category I), two studies assessed morbidity outcomes (category II), two studies assessed outcomes related to symptoms/quality of life/functional status (category III), six studies assessed BP outcomes (category IV), seven studies assessed other clinically relevant surrogate outcomes (category V), and 10 studies assessed physiologic outcomes (category VI) …”
Section: Resultsmentioning
confidence: 99%
“…The consumption of processed food, unlike other developed countries, has been reported as relatively low in Nepal (one in 10 people) . However, a repeat cross‐sectional study in 1981 and 2006 found that the proportion of those consuming a high amount of salt in Nepal increased from 56% to 90%; this increase was reported as one of the highest among LMICs …”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for this phenomenon include the fact that epidemiologic and nutrition transition also affect people from rural regions. In rural areas, initiatives to change dietary behaviour should be implemented in order to reduce cardiovascular risk factors, especially reducing salt intake (34).…”
Section: Discussionmentioning
confidence: 99%